MONITORING OF CHRONIC SINUSITIS USING NASAL NITRIC OXIDE AS A MARKER OF SINUS HEALTH: A SYSTEMATIC REVIEW: Pharmaceutical Sciences - HEALTH - IBRAHIM KARIRI, KHALIL; MAJRASHI, KHALID AHMED; FAGEHI, AHMAD ALI ABDU; HAKAMI, KHALID ALI AWAJI; JABER HAKAMI, AYMAN MOHAMMED; HAMZI, NAWAR AHMED (International Journal of Life Science and Pharma Research, 2019)
It was reported that, nasal nitric oxide (nNO) is continuously released in the paranasal sinuses which acts as antibacterial and antiviral agent and improves mucociliary clearance in sinuses environment. The levels of nasal nitric oxide (nNO) are significantly changed with inflammatory stimuli as well as with medical or surgical treatment for chronic sinusitis. The present systematic review is aimed at evaluating the role of nNO as biomarker for monitoring chronic sinusitis. A web-based search was conducted in MEDLINE with inclusion criteria of human studies in English language that aimed to evaluate the role of nNO as in monitoring chronic sinusitis. Study designs adoptedwereobservational studies or clinical trials with comparisons between patient with chronic sinusitis in study group and control group of patients with flu or healthy population. The outcome assessed was the level of nNO in both groups. Data were collected for characteristics of included study such as study design, sample size, mean age, type and location of sinusitis, and technique and procedures used to monitor nitric oxide. The search on the monitoring of chronic sinusitis using nasal Nitric oxide (nNO) as marker of sinus health resulted in 97 articles, of them 81 articles were irrelevant and six articles were reviews. The included studies in this review were 10 studies. Overall findings showed that significantly lower levels of Nasal NO were reported in the patients with chronic rhinosinusitis (CRS) (irrespective of nasal polyps or allergic rhinitis concomitance) compared to healthy volunteers. The lower levels of Nasal NO in chronic rhinosinusitis are related to the decreasing of NO metabolites. The nasal nitric oxide could be employed as a good biomarker for monitoring the sinus health. The lower levels of nasal NO are indicators to the incidence ofchronic sinus inflammation in patients with chronic rhinosinusitis (CRS) These lower levels of nasal nitric oxide increase significantly after sinus therapy or surgical treatment.